Nest tree characteristics of Grey-headed Woodpeckers (Picus canus) in boreal forests - Pakkala, Timo; Tiainen, Juha; Pakkala, Heikki; Piha, Markus; Kouki, Jari (BirdLife Finland, 2020)
Woodpeckers are important species in forest ecosystems because they make tree cavities that are microhabitats for several other taxa. However, even in boreal areas where most tree cavities are made by woodpeckers, the properties of woodpeckers’nest trees and cavities are poorly known. We studied nest tree characteristics of the Grey-headed Woodpecker (Picus canus) in a 170-km2 forest-dominated area in southern Finland during 1987–2019. The data included 76 nest trees with 80 nest cavities in five different tree species. During the study period, 44% of all nesting attempts were in old cavities.Nestswere found in four forest types, but the proportions of nest tree species differed between them. In all, aspen (Populus tremula) with 70% of nest trees, and with 71% of nest cavities was the dominant cavity tree species. Most nest trees (85%) were dead or decaying, and most cavities (70%) were excavated at visible trunk injury spots. The mean diameter of a nest tree at breast height (DBH) was 37.2 cm and the mean height of a cavity hole was 7.8 m; these were significantly positively correlated. The results highlight the importance of large aspens as nest cavity sites for the species. Conservation and retention of groups of large aspens in main habitats, including clear-cuts, are important for continuous availability of nest trees. This applies particularly to managed boreal forest landscapes where scarcity of suitable trees may be a limiting factor for the species.
Keywords: woodpeckers; forest ecosystems